Understanding transport behaviour and policies to increase walking and cycling - Sulikova, S (2021)
This thesis examined the factors affecting active mobility, walking and cycling, in urban environments using a multilevel perspective, from individual agency to built environment, to national-level policies. Understanding that health behaviour change is complex, and cannot be achieved through a single one-size-fits-all policy is the key premise of this thesis. In order to recognise the system-wide influences on walking and cycling, a socio-ecological framework was developed. This combines insights from psychological literature, transportation, and broader policy, and presents their relative roles and interactions in determining urban transport. Statistical analysis based on data from seven European cities showed the crucial role attitudes and psychosocial variables play in determining active travel. Based on the principles of realist evaluation, an analysis of interventions aimed at changing the psychosocial mindset of study participants in four of the seven cities revealed the short-term positive effects of such soft-measure interventions. However, the analysis also emphasised the need to change people's experiences for these measures to have a lasting effect. Finally, an economic analytical framework was developed to evaluate the potential effectiveness of a nation-wide policy (higher fuel taxes) to reduce car use and increase active travel. While including physical inactivity as a social cost greatly increases the optimal value of a fuel tax, limiting factors such as the psychosocial mindsets of people, or lack of suitable infrastructure, reduce the potential impact of such policies. Hence, working in an integrated, multidisciplinary manner is necessary for changing complex systems such as urban transport, physical activity-related health, and reducing carbon dioxide emissions.